A influência da envoltória no consumo energético de edifícios bancários - Thomaz, Vinicius Falk (Universidade do Vale do Rio dos Sinos, 2019)
Inserted in the scope of energy efficiency in buildings, the purpose of this work is to present studies related to the influence of envelope on the energy efficiency of bank branches. The study seeks to analyze different envelope configurations, suggesting models with better thermal performance and higher energy efficiency than the existing standard. Through computational simulation, this dissertation compares the energy consumption of HVAC systems in the standard envelope model and in the proposed models. The present study also estimates the energy savings by adopting the suggested design and material guidelines, verifying the financial viability and the return on investment time in using the suggested envelopes. Thus, bank agencies that adopted geographic coordinates and climate data of the cities of São Paulo - SP, Belo Horizonte - MG, Porto Alegre - RS, Curitiba - PR, Salvador - BA, Rio de Janeiro - RJ, were defined as objects of study. Florianópolis - SC, Goiânia - GO, Recife - PE, Fortaleza - CE, Belém - PA, Cuiabá - MT, São Luís - MA and Brasília - DF. The method consisted of identifying the standard envelope of the institution's bank buildings for modeling a reference building and energy modelling with the Energy Plus program. Simulations were performed in order to verify the thermal performance and the electric energy consumption for the standard building, later, bioclimatic strategies and changes in the envelope composition were used, generating new simulations and analysis of the advances in the energy efficiency of the studied buildings. Based on the percentage of consumption reduction, the values related to the energy saving were estimated. Adopting the discounted payback method, the return on investment terms were calculated in the adoption of two envelopes of better energy performance. It can be concluded that the suggested envelopes have higher energy efficiency levels than the current standard, with lower power consumption for cooling. The estimated values for energy saving are considerable, with an average value of 24.40% in all simulated cities. Adopting a better performance envelope is economically viable and has a reduced payback time.
Keywords: Eficiência Energética; Arquitetura Bancária; Desempenho térmico; Energy efficiency; Banking Architecture.; Thermal Performance; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo